Pelatihan Penyusunan Portofolio Akademik bagi Dosen Fakultas Ekonomi dan Bisnis Universitas Islam Indragiri untuk Peningkatan Kualifikasi - Widyawati; Muchlis; Syafrinadina; Sri Hidayanti; M Tarmizi; Sri Handayani; Mardiana (Indra Institute Research & Publication, 2025)
Enhancing faculty qualifications is a crucial aspect in improving the quality of higher education. Academic portfolios serve as an essential instrument in faculty career development and qualification enhancement. However, many faculty members still face difficulties in developing effective academic portfolios. This community service project aims to improve the understanding and skills of faculty members at the Faculty of Economics and Business, Universitas Islam Indragiri, in creating academic portfolios. The method employed is an intensive one-day training with a participatory and practical approach. The training covers an introduction to academic portfolio concepts, techniques for documenting academic activities, portfolio development strategies, and hands-on practice. The results of the training show a significant improvement in faculty members' understanding and ability to develop academic portfolios. This activity is expected to contribute to enhancing faculty qualifications and advancing their academic careers.